2006
DOI: 10.1063/1.2173683
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of Pb1−xLaxTiO3 ferroelectric materials from Ti 2p and O 1s soft x-ray absorption spectroscopy

Abstract: The electronic structure of Pb 1−x La x TiO 3 ͑PLT͒ compounds for x ranging from 0 to 30 at. % of La is investigated by means of soft x-ray absorption near edge structure ͑XANES͒ at the Ti L 3,2 and O K edges. The greatest modification in the structure of the Ti 2p XANES spectra of the PLT compounds is observed in the region of the high energy peak of the L 3 edge ͑e g states͒, which exhibits a splitting in the undoped sample. As the amount of lanthanum increases, this splitting becomes less pronounced. This m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 20 publications
4
31
0
Order By: Relevance
“…In lead-based ferroelectric ceramic systems, the ferroelectric character is directly correlated with the electronic properties of both A-site (Pb 2+ ) and B-site (Ti 4+ ) ions [17,18]. Many studies have shown that the density of states (DOS) of oxygen and titanium atoms could provide a more direct correlation with the ferroelectric stability of perovskite-based compounds [19][20][21][22][23][24][25][26][27][28]. They have also reported a significant modification in the hybridization among O 2p, Pb 6sp and Ti 3d states when the ferroelectric character changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In lead-based ferroelectric ceramic systems, the ferroelectric character is directly correlated with the electronic properties of both A-site (Pb 2+ ) and B-site (Ti 4+ ) ions [17,18]. Many studies have shown that the density of states (DOS) of oxygen and titanium atoms could provide a more direct correlation with the ferroelectric stability of perovskite-based compounds [19][20][21][22][23][24][25][26][27][28]. They have also reported a significant modification in the hybridization among O 2p, Pb 6sp and Ti 3d states when the ferroelectric character changes.…”
Section: Introductionmentioning
confidence: 99%
“…In the PLZT and Pb 1Àx Ba x Zr 1Ày Ti y O 3 complex ferroelectric compounds, a reduction in the degree of hybridization between O 2p and Pb 6sp (Ti 3d) states as the amount of La (Ba) increased was directly related to the manifestation of the relaxor character [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Figure a presents the normalized absorption spectra at Ti L 3,2 edges of the N/S‐TiO 2 and pristine TiO 2 . For TiO 2 , the two small peaks at 456–458 eV are related to a transition which is normally forbidden in LS coupling, but becomes allowed due to the multipole pd interactions ,. The separated L 3 and L 2 edges could be assigned to Ti 2 p 3/2 and 2 p 1/2 spin orbit coupling in the Ti 2 p core states, separately .…”
Section: Resultsmentioning
confidence: 97%
“…The order parameter is related to the presence of TiO 6 clusters, whereas the disorder is related to the presence of TiO 5 clusters. It is believed that PL occurs due to interaction of TiO 5 -TiO 6 clusters [20,21]. de Figueiredo et al [22] observed the PL phenomenon in Ca 0.95 Sm 0.05 TiO 3 (CT:Sm) only in disordered structure.…”
Section: Introductionmentioning
confidence: 97%